2012
DOI: 10.1074/mcp.m111.010694
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study of Stepwise Hepatocarcinogenesis From the Model Rats to Patients: Potential Biomarkers Effective for Small Hepatocellular Carcinoma Diagnosis

Abstract: The aim of this study is to find the potential biomarkers from the rat hepatocellular carcinoma (HCC) disease model by using a non-target metabolomics method, and test their usefulness in early human HCC diagnosis. The serum metabolic profiling of the diethylnitrosamine-induced rat HCC model, which presents a stepwise histopathological progression that is similar to human HCC, was performed using liquid chromatography-mass spectrometry. Multivariate data analysis methods were utilized to identify the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 42 publications
3
126
0
Order By: Relevance
“…Five metabolites quinaldic acid, β-sitosterol, arachidyl carnitine, oleamide and tetradecanal were observed for the first time. Nine metabolite lysophosphatidylethanolamines, glycerophosphocholine, LPCs, CDCA glycine conjugate and Lphenylalanine had been reported as serum metabolite biomarkers for HCC diagnosis in previous research [39][40][41].…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 98%
“…Five metabolites quinaldic acid, β-sitosterol, arachidyl carnitine, oleamide and tetradecanal were observed for the first time. Nine metabolite lysophosphatidylethanolamines, glycerophosphocholine, LPCs, CDCA glycine conjugate and Lphenylalanine had been reported as serum metabolite biomarkers for HCC diagnosis in previous research [39][40][41].…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 98%
“…A nontarget metabolomics method was to find the potential biomarkers from the rat HCC disease model and test their usefulness in early human HCC diagnosis. 32 Three metabolites, taurocholic acid, lysophosphoethanolamine 16:0, and lysophosphatidylcholine 22:5 were defined as ''marker metabolites,'' which can be used to distinguish the different stages of hepatocarcinogenesis and represent the abnormal metabolism during the progress of HCC in patients. Moreover, they were also effective for the discrimination of all HCC and chronic LD patients, which could achieve high sensitivity and specificity, better than those of AFP.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 99%
“…As liver-specific metabolites, bile acids are considered to be potential markers related to HCC in many metabolomic studies [59][60][61][62][63]. Recent studies also revealed that some rarely detected bile acids in healthy adults may be potential indicators of HCC, such as fetal bile acids and sulfated bile acids [61][62][63].…”
Section: Primary Liver Cancermentioning
confidence: 99%
“…Bile acids are commonly considered to be indicators of liver injury and may vary during the development of hepatocarcinogenesis [59]. As liver-specific metabolites, bile acids are considered to be potential markers related to HCC in many metabolomic studies [59][60][61][62][63].…”
Section: Primary Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation